PENGARUH PROFITABILITAS, KEPERCAYAAN CEO, FREE CASH FLOW, UKURAN PERUSAHAAN, LIKUIDITAS TERHADAP KEBIJAKAN DIVIDEN - Vivian Puspasari; Yuli Chomsatu Samrotun (J-ISCAN: Journal of Islamic Accounting Research, 2021)
One of the attractions in investing is dividend. Dividend are profit sharing paid to shareholders based on the number of shares owned. The more shares of the company owned by investors, the higher the dividends received by shareholders each period. The purpose of this study is to analyze the effect of profitability, CEO trust, free cash flow, firm size, and liquidity on dividend policy. The sampling technique used was purposive sampling. The sample companies in this study amounted to 31 companies that had met the sampling criteria. Technical analysis of the data used in this study is to use multiple linear analysis. The results of this study indicate that the variables of profitability, CEO trust, free cash flow, firm size, and liquidity have no effect on dividend policy.